2006
DOI: 10.1577/t05-003.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bioenergetics Model Predictions for Fish Undergoing Compensatory Growth

Abstract: A previous evaluation of a bioenergetics model applied to juvenile hybrid sunfish (F1 hybrid of female green sunfish Lepomis cyanellus × male bluegill L. macrochirus) undergoing compensatory growth (CG) indicated that the model substantially overestimated growth and underestimated cumulative consumption. This result suggested that fish bioenergetics models might not adequately account for physiological shifts that occur during CG. However, we demonstrate that application of a recently developed procedure for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
(24 reference statements)
3
16
0
Order By: Relevance
“…The corrective equation we developed significantly reduced model bias and improved the accuracy of consumption estimates. A similar approach was used to improve estimates of cumulative consumption for white crappie (Bajer et al 2004b) and juvenile hybrid sunfish (green sunfish Lepomis cyanellus 3 bluegill L. macrochirus) undergoing compensatory growth (Whitledge et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrective equation we developed significantly reduced model bias and improved the accuracy of consumption estimates. A similar approach was used to improve estimates of cumulative consumption for white crappie (Bajer et al 2004b) and juvenile hybrid sunfish (green sunfish Lepomis cyanellus 3 bluegill L. macrochirus) undergoing compensatory growth (Whitledge et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, consumption-dependent error has been shown to be widespread among bioenergetics models (Madenjian and O'Connor 1999;Bajer et al 2004a, b;Whitledge et al 2006). For age-0 tiger muskellunge, feeding rate and water temperature are known to strongly affect the accuracy of bioenergetics predictions (Chipps et al 2000b).…”
Section: Notementioning
confidence: 99%
“…Compensatory growth by trout was not included in the model. The ability of fish to exhibit an accelerated growth rate to compensate for food deprivation or shortage has been noted widely in captive fish from controlled studies (Abbott & Dill 1989; Whitledge, Hayward, Noltie & Wang 1998; Ali, Nicieza & Wootton 2003; Whitledge, Bajer & Hayward 2006), but information is lacking for wild fish inhabiting streams with limited and seasonal food resources. In addition to the duration of food deprivation influencing weight gain of rainbow trout, past nutritional history, energy content of the diet and whether fish are fed at or below satiation has also been found to influence weight gain and feeding intensity (Jobling & Koskela 1996; Boujard, Burel, Médale, Haylor & Moisan 2000; Ali et al.…”
Section: Discussionmentioning
confidence: 99%
“…Boisclair and Leggett (1989) demonstrated that ACT varied greatly among yellow perch populations, and Post (1990) suggested the use of an ACT of 4 for juvenile yellow perch. In summary, many bioenergetics models have been able to estimate C or G with an ACT from 1 to 2 or by using functions based on swimming speed determined in the laboratory (Stewart et al 1983;Karjalainen et al 1997;Whitledge and Hayward 1997;Madenjian and O'Connor 1999;Madenjian et al 2000;Pääkkönen et al 2003;Whitledge et al 2003Whitledge et al , 2006Chipps and Wahl 2004) or in the field (Worishka and Mehner 1998;Madenjian et al 2000;Pääkkönen et al 2003;Stevens et al 2006). In contrast, Trudel and Rasmussen (2006) suggested that ACT varies widely between populations and that the use of a constant ACT for different lakes is not reliable.…”
Section: Zander Bioenergetics Modelmentioning
confidence: 99%